2000
DOI: 10.1086/316911
|View full text |Cite
|
Sign up to set email alerts
|

Active Intestinal Chloride Secretion in Human Carriers of Cystic Fibrosis Mutations: An Evaluation of the Hypothesis That Heterozygotes Have Subnormal Active Intestinal Chloride Secretion

Abstract: To explain the very high frequency of cystic fibrosis (CF) mutations in most populations of European descent, it has been proposed that CF heterozygotes have a survival advantage when infected with Vibrio cholerae or Escherichia coli, the toxins of which induce diarrhea by stimulation of active intestinal chloride secretion. Two assumptions underlie this hypothesis: (1) chloride conductance by the CF transmembrane conductance regulator (CFTR) is the rate-limiting step for active intestinal chloride secretion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 29 publications
2
36
1
Order By: Relevance
“…However, these theories were disputed by Högenauer et al who measured the in vivo basal and prostaglandinstimulated jejunal chloride secretion in normal subjects, CF heterozygotes, and patients with CF (Hogenauer et al 2000). The results from this study showed that individuals who were heterozygous for CF mutations secreted chloride at the same rate as people without a CF mutation, contradicting the earlier data gained from mouse models.…”
Section: Theories Of Heterozygote Advantagecontrasting
confidence: 92%
“…However, these theories were disputed by Högenauer et al who measured the in vivo basal and prostaglandinstimulated jejunal chloride secretion in normal subjects, CF heterozygotes, and patients with CF (Hogenauer et al 2000). The results from this study showed that individuals who were heterozygous for CF mutations secreted chloride at the same rate as people without a CF mutation, contradicting the earlier data gained from mouse models.…”
Section: Theories Of Heterozygote Advantagecontrasting
confidence: 92%
“…This is consistent with reduced CFTRmediated chloride secretion (15). CF patients, however, continued to secrete chloride even with luminal chloride concentrations as high as 135-140 mEq/l ( Figure 3).…”
Section: Cf Patients Do Not Hyperabsorb Electrolytes and Water Duringsupporting
confidence: 74%
“…It is not known, therefore, if the ion transport abnormalities identified in CF jejunum by in vitro studies would actually result in net hyperabsorption of electrolytes and water in vivo. Although two in vivo studies in humans confirmed reduced active chloride secretion by CF jejunum, both employed test solutions that purposely prevented normal absorptive processes in order to measure the magnitude of active chloride secretion (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore reasonable to believe that heterozygosity for a CFTR functionally silent allele ( ¼ a CF allele) makes the intestinal epithelial cells less prone to secrete Cl À ions and water, as shown in the mouse model, 5 although not confirmed in humans. 6 Chloride transport in vivo in CF heterozygotes is often below 50%, and at times normal, 7 corresponding to the severity of the known mutations. 8 Thus, considering that one of the events required to develop any type of diarrhea is the accumulation of water in the intestinal lumen and that the most severe diarrheas have been caused by cholera, it has been suggested that:…”
Section: Nature Of the Cftr þ /Cftr Cf Heterozygote Advantagementioning
confidence: 99%